The Role of Digitalization in Moderating the Impact of Location, Labor, and Capital on the Productivity of Micro Culinary Businesses in Surabaya - Ilfi Ayu Lestari; Hadi Sumarsono; Agus Sumanto (Eduvest - Journal of Universal Studies, 2026)
Micro-culinary enterprises have a strategic role in the urban economy but still face challenges of low productivity due to limited utilization of production factors and operational efficiency. This research aims to analyze the influence of location, labor, and capital values on the productivity of culinary micro-businesses in the city of Surabaya and to examine the role of digitalization in reducing business technical inefficiency. The analysis employed Stochastic Frontier Analysis (SFA) with a Cobb–Douglas production function, using primary survey data from culinary micro-enterprises in Surabaya. The estimation results show that location, labor, and capital each have a positive and significant effect on productivity. Location value is the most dominant factor, followed by capital and labor. The technical efficiency analysis indicates that the average efficiency level of culinary micro businesses is 0.8629, which suggests that business actors have operated quite efficiently but still have the potential to increase productivity by 13.71%. Digitalization has been shown to play a significant role in reducing technical inefficiencies, even though it does not have a direct influence on productivity increases. Digitalization strengthens the utilization of production inputs by increasing the operational efficiency of marketing and business management. Increasing the productivity of culinary micro businesses depends not only on increasing production inputs but also on strengthening business efficiency through the use of digital technology. The micro business development strategy needs to be directed toward improving input quality as well as accelerating digital transformation to foster sustainable business competitiveness.